Menuju Usaha Berkelanjutan: Membina UMKM Pemula dengan Produk Hijau dan Strategi Digital - Maria Esther, Astrid; Kurniawati; Virna sulfitri; M. Yudhi Lutfi (PT. Cendekia Sapta Indonesia, 2025)
Sustainable business development through green entrepreneurship and digital transformation is a vital solution to enhance the economic independence of youth under social care. This community service program was conducted at the Youth Social Rehabilitation Center (PSBR) Rusun Rawa Bebek, Cakung, East Jakarta, on July 7, 2023, involving 38 participants (17 female and 21 male), most of whom had junior high school education backgrounds. The program aimed to foster entrepreneurial spirit among beginners by introducing the concepts of eco-friendly products (green products) and digital marketing strategies. The methods included lectures, interactive training, group discussions, and Q&A sessions. Preliminary evaluation indicated strong enthusiasm, with 55.3% of participants reporting that the material matched their needs and 52.6% finding the sessions easy to understand. These results demonstrate an increase in participants’ comprehension of green entrepreneurship and digital-based marketing strategies. The program provides a foundation for further capacity-building activities such as developing simple business plans and mentoring digital marketing practices, thereby strengthening entrepreneurial interest and capabilities among beginner entrepreneurs.